A pan-cancer analysis of the expression of STAT family genes in tumors and their relationship to the tumor microenvironment - Zhou, Min; Zhang, Ping; Da, Mengting; Yang, Rui; Ma, Yulian; Zhao, Jiuda; Ma, Tao; Xia, Jiazeng; Shen, Guoshuang; Chen, Yu; Chen, Daozhen (Frontiers in Oncology, 2022)
Background: The signal transducer and activator of transcription (STAT) protein family , a group of 7 members (STAT1, 2, 3, 4, 5A, 5B and 6), has been widely used to investigate numerous biological functions including cell proliferation, differentiation, apoptosis and immune regulation. However, not much is known about the role of the STAT family genes in pan-cancer. Methods: TIMER, Sangerbox, cBioPortal, GSCALite, Xena Shiny, GeneMANIA, GEPIA and Metascape were used to analyze the relationship between STAT gene expression, clinical outcome, gene variation, methylation status, pathway activity, tumor immune infiltration and microenvironment in different cancer types and screened drugs that could potentially influence STATs. Results: The Cancer Genome Atlas (TCGA) pan-cancer data showed that most STAT family genes were extensively changed in most tumors compared to the adjacent normal tissues. We also found that STAT gene expression could be used to predict patient survival in various cancers. STAT gene family formed a network of interaction networks that was associated with several pathways. By mining the GDSC database, we discovered a number of potential drugs that might target STAT regulators. Importantly, the close correlation between STATs and immunocell infiltration suggested the important role of dysregulation of STATs in tumor immune escape. Finally, the relation between STAT gene expression and tumor microenvironment (TME) indicated that the higher expression of STAT regulators, the higher the degree of tumor stem cells. Conclusion: Considering these genomic alterations and clinical features of STAT family members across cancer types, it'll be possible to change the relationship between STATs and tumorigenesis. It was beneficial to treat cancer by targeting these STAT regulators.